2008
DOI: 10.1590/s0036-36342008000700015
|View full text |Cite
|
Sign up to set email alerts
|

Injury prevention and control: reflections on the state and the direction of the field

Abstract: Objective. To provide an assessment of the contours of the injury field today and to raise questions about our future direction. Material and Methods. We classified the selfreported activities of injury centers, assessed trends in injuryrelated publications in peer review journals, and compared data on current funding levels. Results. The 47 identified centers are more likely to focus on unintentional injuries and on prevention than on intentional injuries, biomechanics, acute care or rehabilitation. Injury-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This could be explained by inadequate physical preparation, technical errors in athletic gestures, inadequate equipment or playing fields. 16 , 35 , 36 In a recent review, Bernardino et al studied padel injuries in both professional and amateur players and found an injury rate of 40-70% for players who suffered at least one injury in a year of practice. 15 Interestingly, the same authors showed a general predominance of muscle injuries in the lower limbs, particularly in male players, with a higher number of upper limb injuries in female players.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by inadequate physical preparation, technical errors in athletic gestures, inadequate equipment or playing fields. 16 , 35 , 36 In a recent review, Bernardino et al studied padel injuries in both professional and amateur players and found an injury rate of 40-70% for players who suffered at least one injury in a year of practice. 15 Interestingly, the same authors showed a general predominance of muscle injuries in the lower limbs, particularly in male players, with a higher number of upper limb injuries in female players.…”
Section: Discussionmentioning
confidence: 99%
“…The subsidized regime is equivalent worldwide to health systems financed by the state through taxes, its accessibility to health services is limited and most of the population belongs to this regime. 19,20 For the local management of ulcers, this type of treatment is very variable and dynamic considering the different states of the natural healing process: necrotic, fibrinous, exudative, infectious, granulation and/or epithelialization. The protocols managed by the two regimes of the Health System are based on the aforementioned guidelines using different types of dressings depending on the injury, 6 varying the time between healing sessions, depending on the group of dressings used, which can range from 3 to 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel mundial los accidentes viales son responsables de importantes costes personales, familiares y sanitarios tanto en el pasado siglo XX y como en el presente XXI, particularmente en los países con bajos o medios ingresos económicos (consume entre 1 y 2% de su Producto Interno Bruto). Igualmente la Organización Mundial de la Salud (OMS) estima que los accidentes viales se constituirán en la quinta causa de mortalidad a nivel mundial para el año 2030, por ello, deben ser sujeto del análisis, con el objeto de minimizar su magnitud y transcendencia, dada su comprobada vulnerabilidad a las estrategias educativas dentro del contexto de la promoción de la salud [1][2][3][4][5][6][7][8] .…”
Section: Introductionunclassified